Estudio del uso del Dinero Electrónico en las Categorías de la Cámara de Comercio año 2015, de la Ciudad de Loja - Maza Jumbo, Paulina del Carmen (2017)
4 SUMMARY The analysis of the use of electronic money by merchants registered in the Chamber of Commerce of the City of Loja is the axis of this thesis, so it is necessary to investigate how it has impacted the economy of the Lojana, This new system of payment. This medium has been implemented in the Ecuadorian economy since the year 2014, and promoted by the Central Bank of Ecuador, proving to be an important and interesting project, directing its users to its efficiency and sustainability objectives. Social and financial inclusion. Because of this situation, the investigation details the mechanism of use of electronic money in the commercial locations of the city of Loja Within the methodological process used, this study began with the search of relevant data for the analysis of this financial tool, using entities, people and bibliographic documents. To this was added the investigation of the experiential cases of different countries of the world that have applied this electronic means of payment in their economies, studying their advantages and disadvantages, knowing in itself, what has been the contribution to the liquidity of these countries . Also, the legal resolutions, operation, composition and regulation of the Electronic Money System were taken into consideration. This study of the use of electronic money in the categories determined by the Chamber of Commerce in the Year 2015, of the City of Loja, demonstrating the places, the type of activities and the goods and services that Are exchanged using the electronic money system. All this is achieved with the identification of establishments, determination of compliance level and the elaboration of a diagnosis through a SWOT matrix, on the application of electronic money in the City of Loja. Finally, we highlight the main conclusions and recommendations, highlighting the most relevant aspects to give consideration to the people who can read this investigative work, a glossary of terms available and successful, the respective index of topics that Refer to indicate the structure of thesis work and the main bibliographic sources.